2017
DOI: 10.1111/jocn.13680
|View full text |Cite
|
Sign up to set email alerts
|

Experience and nursing needs of school‐age children undergoing lumbar puncture during the treatment of acute lymphoblastic leukaemia: a descriptive and qualitative study

Abstract: The experiences described in this study contribute to a better understanding of the needs of acute lymphoblastic leukaemia children undergoing lumbar puncture. They also provide valuable information to professional medical care staff that develops future nursing assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Children’s drawings depict sadness as associated with social isolation, separation from siblings, grief, and extending to other family members (Linder, Bratton et al, 2018; Sadruddin & Hameed-ur-Rehman, 2013). School-age children receiving treatment for ALL also experienced sadness in response to lumbar punctures (Xie et al, 2017). Sadness was a prevalent theme of concern among AYAs at the time of diagnosis (Korsvold et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children’s drawings depict sadness as associated with social isolation, separation from siblings, grief, and extending to other family members (Linder, Bratton et al, 2018; Sadruddin & Hameed-ur-Rehman, 2013). School-age children receiving treatment for ALL also experienced sadness in response to lumbar punctures (Xie et al, 2017). Sadness was a prevalent theme of concern among AYAs at the time of diagnosis (Korsvold et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The experience of sadness was common across age-groups and across countries. Children experienced multiple sources of sadness, including treatment-related procedures as well as a sense of isolation and grief (Linder, Bratton, et al, 2018; Sadruddin & Hameed-ur-Rehman, 2013; Xie et al, 2017). Although the prevalence of sadness decreases over the course of treatment and over a cycle of chemotherapy (Hockenberry et al, 2014), persistent sadness, when it occurred, was of greater severity and associated distress (Baggott et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…,[22][23][24][27][28][29]31,33,35,37,40,41,43,44,47,56,57,97,[100][101][102][103][107][108][109][110][111][112][113][114] Fear and Worry for the Future Paralyzed by devastating news • At first I did not think I was sick at all, I thought they had mixed up the tests. But after becoming better from the medication I was aware that I was sick, but I did not want to understand it 29.…”
mentioning
confidence: 99%
“…[9][10][11]20,21,24,30,33,35,[41][42][43]46,50,51,56,61,94,96,101,105,106,112,115,116,118,120,122,126,136 from the same spot every time. 21 10,11,20,21,23,24,39,41-43,47,49,52,58-61,97,105,115,116,119,120, 122,124,129,136,139,140 .…”
mentioning
confidence: 99%
“…Fear and attachment: According to the ndings of this study, for children with leukemia between 2 and 7 years old, medical staff should pay attention to their emotional reactions during hospitalization, and rst ensure a comfortable and warm environment when conducting diagnosis and treatment. Anwei Xie [21] found that children with leukemia hoped that pictures of kids could be hung on the wall during waist puncture, and that medical staff could wear overalls with colorful cartoon patterns, which may eliminate the children's fear on the hospital environment and medical staff. Liu Qun [22] stated that the implementation of comfort care could obviously eliminate the nervousness and fear of children with leukemia, and medical staff should pay attention to a kind attitude and establish a trusting relationship with the children, increasing the children's sense of security and improving their attachment mood.…”
Section: Discussionmentioning
confidence: 99%